Multifunctional PLGA-based nanoparticles as a controlled release drug delivery system for antioxidant and anticoagulant therapy - Lee, Pei-Chi; Zan, Bo-Shen; Chen, Li-Ting; Chung, Tze-Wen (International journal of nanomedicine, 2019)
Ischemia/reperfusion (I/R) injury causes the generation of many ROS such as H O and leads to vascular thrombosis, which causes tissue damage. In this investigation, poly (lactideco-glycolide) (PLGA)-based nanoparticles are used for their anticoagulant and antioxidant properties in vascular therapy. Both heparin and glutathione are entrapped on PLGA-stearylamine nanoparticles by layer-by-layer interactions. The drug release rate is successfully controlled with only 10.3% of the heparin released after 96 hours. An H O -responsive platform is also developed by combining silk fibroin and horse peroxidase to detect H O in this drug delivery system. Besides, hyaluronic acid was decorated on the surface of nanoparticles to target the human bone marrow mesenchymal stem cells (hBMSCs) for cell therapy. The results of an in vitro study indicate that the nanoparticles could be taken up by hBMSCs within 2 hours and exocytosis occurred 6 hours after cellular uptake. We propose that the multifunctional nanoparticles that are formed herein can be effectively delivered to the site of an I/R injury via the hBMSC homing effect. The proposed approach can potentially be used to treat vascular diseases, providing a platform for hBMSCs for the controlled delivery of a wide range of drugs.